POLA KALIMAT DALAM TAJUK RENCANA KOMPAS EDISI MARET 2015 - M.G. Banon Fitri Wahjuni (Universitas Bengkulu, 2017)
The general purpose of this research is to know the Sentence Pattern in Editorial of Kompas Newspaper in March 2015 Edition. The specific purpose is to describe the simple sentence pattern, compound sentence pattern, complex sentence pattern and the combined sentence pattern in the editorial of Kompas newspaper in March 2015 edition. This thesis uses a descriptive method with the research data in the form of simple sentence and compound sentence taken from the editorial of Kompas Newspaper in March 2015 edition. The editorial of Kompas in March 2015 edition contains a simple sentence that has 10 variations of sentence pattern, that are S – P, S – P – O, S – P – Adverb, S – P – O – Adverb, S – P – Complement, S – P – O – Complement, P – S, S – Adverb – P, Adverb – S – P, Adverb – S – P – O.Compound sentence generally uses the variation of sentence pattern as the following S1 – P1 + S2 – P2 and S – P1 + P2 – O. Complex sentence generally uses the following variations of sentence pattern S1 : (s2 – p2) – P1, S1 – P1 – O - : (s2 – p2), and S – P – O – K : (s2 – p2). While the mixed sentence uses the combination of the compound sentence patter and complex sentence pattern K – S1 – P1 – O: (s2 – p2 + p3) – K : ( p4 – o ) and S1:(s2 – p2 – o) – P1: (p3- o: p4 + p5 – k ). Kata Kunci: Sentence Pattern and The editorial of Kompas